2019 IEEE 13th International Symposium on Applied Computational Intelligence and Informatics (SACI) 2019
DOI: 10.1109/saci46893.2019.9111599
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Robot-Assisted Surgery: Soft Tissue Contact Identification

Abstract: Robot-Assisted MinimallyInvasive Surgery (RAMIS) is becoming standard-of-care in western medicine. RAMIS offers better patient outcome compared to traditional open surgery, however, the surgeons' ability to identify the tissues with the sense of touch is missing from most robotic systems. Regarding haptic feedback, the most promising diagnostic technique is probably palpation; a physical contact examination method through which information can be gathered about the underlying structures by gently pressing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Taking the angle α in Equation (7) as the independent variable, the schematic image of Δf-α function is shown in Figure 4. To optimize the performance of the sensor, two goals of sensor parameters optimization are: (1) As shown in Figure 4, the difference between Δf 0°and Δf 45° is close to 0 (D1 is close to 0), to ensure that the angle change has the smallest impact on the detection result. (2) When tissues with different stiffness are tested, the difference between Δfi and Δfj should be larger than D1 to ensure that they can be reliably distinguished, as shown in D2 in Figure 4.…”
Section: A New Detection Methods and Its Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the angle α in Equation (7) as the independent variable, the schematic image of Δf-α function is shown in Figure 4. To optimize the performance of the sensor, two goals of sensor parameters optimization are: (1) As shown in Figure 4, the difference between Δf 0°and Δf 45° is close to 0 (D1 is close to 0), to ensure that the angle change has the smallest impact on the detection result. (2) When tissues with different stiffness are tested, the difference between Δfi and Δfj should be larger than D1 to ensure that they can be reliably distinguished, as shown in D2 in Figure 4.…”
Section: A New Detection Methods and Its Optimizationmentioning
confidence: 99%
“…Since the lumps are often harder than the surrounding normal tissues, doctors can usually directly distinguish the lump by the difference in stiffness felt. [ 1 , 2 ] In order to distinguish different stiffness in RMIS, a tactile sensor for tissue stiffness detection is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of force applied to the tissues is a significant characteristic of surgery; it is important not to cause damage by excessive force, but it is also crucial to provide enough tension e.g., during tightening a knot [ 65 , 66 ]. Additionally, Trejos et al [ 53 ] have shown in their experimental study that force-based metrics correlate better with experience levels than temporal metrics in manual MIS.…”
Section: Performance Metricsmentioning
confidence: 99%
“…For the proposed concept to operate properly, the indenter must be completely submerged in the sample. To do this, the material properties of the sample under investigation are important [8]. For example, the proposed concept cannot be applied to dense materials such as bone.…”
Section: Accuracymentioning
confidence: 99%